Topical Epigallocatechin Gallate (EGCG) 1% for Chronic Plantar Ulcers in Leprosy - Riyana Noor Oktaviyanti; Cita Rosita Sigit Prakoeswa; Diah Mira Indramaya; Esti Hendradi; Sawitri Sawitri; Linda Astari; Damayanti Damayanti; Muhammad Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Chronic plantar ulcers in leprosy (CPUL) increase morbidity, increase medical costs, cause loss of productivity, and decrease quality of life. CPUL is a severe complication of leprosy disease with a 10-20% incidence. In general, CPUL consume a significant amount of time to heal. Green tea extract contains high amount of Epigallocatechin gallate (EGCG). EGCG functions as antiinflammatory, antimicrobial, and immunomodulator. This suggests that EGCG is effective for dermal wound treatment by facilitating reepithelialization. Purpose: To investigate the effect of topical EGCG 1% on the CPUL healing process. Methods: The topical EGCG 1% were applied every three days for eight weeks. Size of the ulcers, side effects and possible complications were monitored weekly. Result: There were significant clinical and statistical differences in the size and depth of the ulcers (p=0.000), as observed in the EGCG group. There was no side effect and complication found. Conclusions: Topical EGCG 1% was effective for CPUL healing. Sixty three point six percent of the ulcers were clinically healed, 31.8% demonstrated improvement, and 4.6% no effect was observed.